Academic Salaries and Contracts: What Do We Know? - Altbach, Philip; Pacheco, Ivan (International Higher Education, 2012)
Data in this article are from Paying the Professoriate: A Global Comparison of Compensation and Contracts, ed- ited by Philip G. Altbach, Liz Reisberg, Maria Yudkevich, Gregory Androushchak, and Iván F. Pacheco (New York: Routlege, 2012). Additional data can be found on the project Web site: http://acarem.hse.ru. This research resulted from a collaboration between the Center for International Higher Education at Boston College and the Laboratory of Institutional Analysis at the National Research University Higher School of Economics, Moscow, Russia.